Crustal and Lithospheric Variations along the Western Passive Continental Margin of the Indian Peninsula - Prasad, Muthyala; Dubey, Chandra P. (Global Journal of Earth Science and Engineering, 2023)
The western passive continental margin (WPCM) of the Indian Peninsula is one of the world’s largest and most remarkable escarpments, signifying a boundary between oceanic and continental lithospheres. It traverses distinct lithological units, majorly the SGT, WDC, and DVP, each characterized by distinct geological structures, geochronological histories, and petro-physical properties. Despite numerous research efforts, the exact mechanisms governing the WPCM evolution and its developmental connections remain unclear due to limited data and significant uncertainties. In our study, we meticulously analyzed global and local models, focusing on the Western Ghats (WG), to examine crust and lithosphere thickness. Our analysis revealed significant uncertainties in crustal and lithospheric variations, with a maximum difference of 10.68% in crust thickness and 20.04% in lithospheric thickness across different major lithological formations in the WG. These differences can have a substantial impact on the geodynamic analysis of lithospheric structures and tectonic evolution. Additionally, we developed a 2-D lithospheric density model over the WG, crossing the major geological units, which delineates the crust and lithospheric structure between the eastern and western sides of the escarpment. Our results, in conjunction with geomorphological data, suggest that the WPCM’s thick lithosphere with elevated topography illustrates a continuous upwarp, supported by flexural compensation of uplifted terrain. The movement of the Indian plate, primarily in the N-S and NW-SE directions, subsequently modified the entire escarpment. This model offers insights into the evolution of the WPCM and potentially contributes to the formation of the NE-SW fault in the southern part of the South Indian Shield, with potential implications for the Palghat gap.